Preparation and evaluation of heavy metal rejection properties of polyetherimide/porous activated bentonite clay nanocomposite membrane - Ismail, Ahmad Fauzi (Royal Society of Chemistry, 2014)
The acid activated bentonite clay ranging from 1.0 to 4.0 wt% was incorporated into polyetherimide membranes and was extensively studied for its morphology, porosity, membrane hydraulic resistance and hydrophilic properties. The nanocomposite membrane has shown an increment in porosity, hydrophilicity and a reduction in hydraulic resistance. Elemental mapping studies confirmed the intercalation of activated bentonite clay within the polymer matrix. Studies have been conducted to analyse the permeate flux and rejection of Cu(ii), Ni(ii) and Cd(ii) ions by varying the pH and initial feed concentration. The results revealed that membranes with higher clay dosage showed enhanced flux and rejection, whereas lower rejection was observed in the case of lower pH and higher initial feed concentrations. It has also been demonstrated that the affinity of metal ions to form the hydration sphere and the adsorption capacity towards bentonite clay plays a vital role in the effective removal of metal ions. The membrane showed good rejection of heavy metal ions without any external chelating agent. The membranes showed maximum rejection of 69.3%, 76.2% and 82.5% for 250 ppm of Cd(ii), Ni(ii) and Cu(ii) ion solutions, respectively. The low level of heavy metal concentration in the permeate indicates that good quality water could be reclaimed for further reuse.